The role and involvement of dads in the lives and education of their children with special educational needs and/or disabilities within an early intervention context - Mc Guckin, Conor; Ren, Ke (My University, 2022)
This literature review prefaced a research project that explored dads’ role and involvement in the lives and education of their children with special educational needs and/or disabilities (SEN/D) within the context of early intervention (EI) (see Ren & Mc Guckin, 2022). We present a comprehensive, critical, and analytical review of the literature regarding the area of dad involvement in EI provided for children with SEN/D and their families. To conduct this review, key terminology was used to search in well-known, widely recognised, and distinguished research databases (e.g., Education Full Text, PsycINFO, Web of Science). The search yielded 112 results, from which 21 final articles were selected for inclusion. To begin, the historical perspective of fatherhood and dad involvement in the childbearing family is reviewed. This provides a necessary context for a deeper understanding of the central issues related to this area. To provide an explanation of the ways in which contemporary dads are influential, the review then explores the role and function of dads and their contributions to their child’s developmental outcomes. Such an exploration leads to a necessary critical review of recent research findings related to dads’ involvement in the lives of children with SEN/D and EI. This comprehensive review extends our knowledge in understanding the role and involvement of dads' contributions to the outcome of their families and their children with SEN/D, particularly within an EI context.
PUBLISHED
Keywords: Dad-role; Involvement; Children with disabilities; Early intervention; Inclusive Society; Changing Fathers; Child and adolescent health; EDUCATION; Early Intervention; FATHERS; Handicapped Early Intervention; fathers role